(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: There has been a dramatic increase in the interest X Practice of Laparoscopic urological procedures. Leparoscopic Nephectomy for both Berign and Melignant Diseases of Kidney is incuesingly being performed. The aim of the study to evaluated the results of our initial experiences of laparoscopic nephrectomy cases performed in patients with local and locally advanced renal cell carcinoma. Materials and methods: It was a retrospective study. From July 2020 to July 2023, 17 patients underwent laparoscopic nephrectomy for local and locally advanced renal cell carcinoma. The duration of operation , blood loss, total hospital stay, perioperative complications and follow-up time were evaluated. Results: The mean age of the patients was 56.8 (33-72). Mean duration of operation was 140.4 (75-190) minutes and the duration of hospital stay was 3.2 (2-5) days. Renal vein thrombus in 3 patients perirenal fat tissue invasive in 9 patients. In 2 patients, the tumor exceeded the fascia gerota. The mean follow-up period was 18.3 (6-42).Two patients had lung metastasis during follow- up. Two patients died in the 5th and 36th months following the operation. Conclusion: Radical nephrectomy improves the survival in patients with local and locally advanced renal tumors. Although laparoscopic approach has some difficulties in these patients but the minimal invasive treatment can be safely performed by experienced surgeons. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 20-23